2018
DOI: 10.1111/jmi.12764
|View full text |Cite
|
Sign up to set email alerts
|

FIB‐SEM imaging properties of Drosophila melanogaster tissues embedded in Lowicryl HM20

Abstract: Summary Lowicryl resins enable processing of biological material for electron microscopy at the lowest temperatures compatible with resin embedding. When combined with high‐pressure freezing and freeze‐substitution, Lowicryl embedding supports preservation of fine structural details and fluorescent markers. Here, we analysed the applicability of Lowicryl HM20 embedding for focused ion beam (FIB) scanning electron microscopy (SEM) tomography of Drosophila melanogaster embryonic and larval model systems. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 78 publications
3
7
0
Order By: Relevance
“…Our work shows that sample preparation protocols compatible with fluorescence preservation are satisfactory for FIB-SEM milling and imaging. In agreement with a previous report (Porrati et al, 2019), we achieved good contrast in the presence of 0.1% UA and complete absence of osmium. The stability and milling properties of Lowicryl HM20 under the FIB were comparable to the commonly used epoxy resins.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our work shows that sample preparation protocols compatible with fluorescence preservation are satisfactory for FIB-SEM milling and imaging. In agreement with a previous report (Porrati et al, 2019), we achieved good contrast in the presence of 0.1% UA and complete absence of osmium. The stability and milling properties of Lowicryl HM20 under the FIB were comparable to the commonly used epoxy resins.…”
Section: Discussionsupporting
confidence: 93%
“…Recent publications showed good results in FIB-SEM acquisition of samples that were high-pressure frozen, freeze substituted (FS) with low amounts of UA, and embedded in acrylic resins (Höhn et al, 2015;Porrati et al, 2019). Based on these observations, we have established an easy and robust workflow that allows targeted FIB-SEM imaging of fluorescently labeled structures in a large volume (∼3.14 mm 2 × 0.2/0.4 mm depth).…”
Section: Introductionmentioning
confidence: 90%
“…As most microalgae display characteristic autofluorescent properties, we decided to utilize light microscopy to target specific cells of interest. We therefore performed a freeze substitution method for preserving fluorescence by using a low amount of heavy metals and embedding in Lowicryl HM20 (Kukulski et al, 2011; Nixon et al, 2009; Porrati et al, 2019; Ronchi et al, 2021). Confocal 3D imaging of the resulting block revealed that the autofluorescence pattern was preserved after sample preparation and could be detected in the block for the entire thickness of the HPF material (200 µm) (Fig 1A, Video S1).…”
Section: Resultsmentioning
confidence: 99%
“…Recent publications showed good results in FIB-SEM acquisition of samples that were high pressure frozen, freeze substituted with low amount of UA and embedded in acrylic resins (Höhn et al, 2015; Porrati et al, 2019). Based on these observations and on our previously established sample preparation protocols for on-section CLEM of tissues (Hampoelz et al, 2016, 2019; Wong et al, 2020; Lee et al, 2020), we have established an easy and robust workflow that allows targeted FIB-SEM imaging of fluorescently labelled structures in a large volume (~7mm 2 x 200/400 μm depth).…”
Section: Introductionmentioning
confidence: 99%